Italian renaissance art - Adams, Laurie Schneider (New York, N.Y. Routledge, 2018)
The chronology of the Italian Renaissance, its character, and context have long been a topic of discussion among scholars. Some date its beginnings to the fourteenth century work of Giotto, others to the generation of Masaccio, Brunelleschi, and Donatello that flourished from around 1400.

The close of the Renaissance has also proved elusive.

Mannerism, for example, is variously considered to be an independent (but subsidiary) late aspect of Renaissance style or a distinct style in its own right.
Keywords: Art, Renaissance -- Italy; Art, Italian